2011
DOI: 10.1007/s11069-011-9807-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of a GIS-aided method for the assessment of volcaniclastic soil sliding susceptibility to sample areas of Campania (Southern Italy)

Abstract: A significant part of Campania is extensively covered by volcaniclastic soils, deriving from the alteration of airfall-sedimented formations of layered ashes and pumices that were ejected by Campi Flegrei and Mt. Somma–Vesuvius during explosive eruptions.\ud Where such soils cover steep slopes cut in carbonate bedrock, landforms depend essentially on the morpho-evolution of such slopes prior to the deposition of the volcaniclastic soils, because these are generally present only as thin veneers, up to a few met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Flash floods are very dangerous, often resulting in the loss of life due to the fact that they can deliver enormous amounts of water and debris in a very short space of time (Gaume et al, 2009;Tarolli et al, 2012). These events, normally, have a special impact in mountain areas, where the effects of extreme precipitations are heightened by slope steepness (Calcaterra et al, 2003;Fiorillo et al, 2001;Lebel et al, 2011;Pereira et al, 2010;Perriello Zampelli et al, 2012). However, coastal environments with mountain-like geomorphological features can also be seriously exposed to accelerated erosion and landslide and flood risks (Guthrie and Evans, 2004;Cevasco et al, 2010;Santo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Flash floods are very dangerous, often resulting in the loss of life due to the fact that they can deliver enormous amounts of water and debris in a very short space of time (Gaume et al, 2009;Tarolli et al, 2012). These events, normally, have a special impact in mountain areas, where the effects of extreme precipitations are heightened by slope steepness (Calcaterra et al, 2003;Fiorillo et al, 2001;Lebel et al, 2011;Pereira et al, 2010;Perriello Zampelli et al, 2012). However, coastal environments with mountain-like geomorphological features can also be seriously exposed to accelerated erosion and landslide and flood risks (Guthrie and Evans, 2004;Cevasco et al, 2010;Santo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The common approaches used to define susceptibility maps of rainfall-induced flowtype landslides in this area consider geomorphological and stratigraphic factors including slope angle, cover thickness and presence of natural or artificial discontinuities [84,86]. However, the highly variable and contrasting hydraulic properties of ash-fall pyroclastic soil horizons can impact the modeling of infiltration processes and thus storage dynamics and pore water pressure distribution [33,[110][111][112].…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, some authors identified the basic factors controlling the susceptibility to initial landsliding, which were recognized in small-scale specific geomorphological and anthropogenic features, such as knickpoints, morphological discontinuities related to outcropping carbonate rocky cliffs and artificial cuts into the pyroclastic mantle, excavated for the construction of mountain roads [67,75,76,[81][82][83][84][85][86]. Given the undoubted cause/effect relationship between landslide triggering and rainfall patterns [87][88][89][90][91], the comprehension of temporal and spatial hydrological dynamics is a key factor to understand the landslide triggering processes into these layered soils, which can store a large amount of water over the pressure-head interval ranging between the field capacity and the permanent wilting point [33].…”
Section: Flow-type Landslides Involving Ash-fall Pyroclastic Coveringsmentioning
confidence: 99%
“…Up to now, several algorithms and models have been proposed for generating landslide susceptibility, mainly including Analytical Hierarchy Process-(AHP) (Khezri, 2010), Logistic Regression (Carrara, 1983), Fuzzy Logic (Gee, 1991), Artificial Neural Network (ANN) analysis (Caniani et al, 2008), modeling approaches (Perriello Zampelli et al, 2012), Fuzzy Analytical Hierarchy Process (Liu et al, 2007), Geographically weighted principal component analysis (Faraji Sabokbar et al, 2014) etc., most of which are related to the weight of landslide factors. So, undoubtedly, the above studies demonstrate that many techniques have been used for landslide susceptibility mapping and have achieved excellent results.…”
Section: Introductionmentioning
confidence: 99%